Intratumoral modulation of the inducible co-stimulator ICOS by recombinant oncolytic virus promotes systemic anti-tumour immunity - Dmitriy Zamarin (Nature Portfolio, 2017)
Oncolytic viruses induce a variety of immune targets in the infected tumours. Here, the authors show that Newcastle Disease Virus (NDV) upregulates the inducible co-stimulator (ICOS) on T cells and that intratumoral targeting of ICOS with engineered NDV in combination with CTLA-4 blockade induces systemic anti-tumour immunity in mice.